2016
DOI: 10.1016/j.jtho.2015.10.020
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Light Dose for Photodynamic Therapy Using 2-[1-Hexyloxyethyl]-2 Devinyl Pyropheophorbide-a for the Treatment of Non–Small Cell Carcinoma In Situ or Non–Small Cell Microinvasive Bronchogenic Carcinoma: A Dose Ranging Study

Abstract: Introduction We report a phase I trial of photodynamic therapy (PDT) of carcinoma-insitu (CIS) and microinvasive cancer (MIC) of the central airways with the photosensitizer (PS) 2-[1-hexyloxyethyl]-2-devinyl pyropheophorbide-a (HPPH). HPPH has the advantage of minimal general phototoxicity over the commonly used PS porfimer sodium (Photofrin®). Methods The objectives of this study were 1) to determine the maximally tolerated light dose at a fixed PS dose and 2) to gain initial insight into the effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…HPPH is a chlorin based PS which absorbs light at 665 nm and has a lower risk of skin sensitivity due to its shorter half-life compared to Photofrin ® [ 144 ]. A Phase I dose escalation study showed HPPH-PDT is capable of achieving high rates of CR that is retained for months in patients with carcinoma in situ (CIS) and micro invasive cancer (MIC) of the central airways [ 145 ]. Minor photosensitivity was reported but overall AEs were limited.…”
Section: Pdt In Clinical Trialsmentioning
confidence: 99%
“…HPPH is a chlorin based PS which absorbs light at 665 nm and has a lower risk of skin sensitivity due to its shorter half-life compared to Photofrin ® [ 144 ]. A Phase I dose escalation study showed HPPH-PDT is capable of achieving high rates of CR that is retained for months in patients with carcinoma in situ (CIS) and micro invasive cancer (MIC) of the central airways [ 145 ]. Minor photosensitivity was reported but overall AEs were limited.…”
Section: Pdt In Clinical Trialsmentioning
confidence: 99%
“…Also,t his compound is soluble in water and activated using red light, whereas most PACT compounds reported to date require UV, blue or green light for activation. Thes teric hindrance of [2]Cl 2 is high enough to obtain activation using clinically relevant red-light doses (21 Jcm À2 ), [28] but low enough to maintain thermal stability.I nc ontrast, [1]Cl 2 is too labile in the dark, which make it unsuitable for PACT.Altogether this study represents the first example of PACT where the phototoxicity index measured in hypoxic cancer cells with red light can be explained by al ow 1 O 2 quantum yield, an efficient oxygen-independent photosubstitution reaction, and enzyme inhibition.…”
Section: Zuschriftenmentioning
confidence: 99%
“…Also, this compound is soluble in water and activated using red light, whereas most PACT compounds reported to date require UV, blue or green light for activation. The steric hindrance of [ 2 ]Cl 2 is high enough to obtain activation using clinically relevant red‐light doses (21 J cm −2 ),28 but low enough to maintain thermal stability. In contrast, [ 1 ]Cl 2 is too labile in the dark, which make it unsuitable for PACT.…”
mentioning
confidence: 99%
“…Given that PLZ4 also interacts with integrin αvβ3, it would be interesting to explore the potential similar vascular effects through PLZ4-tumor endothelial cell interaction. Additionally, another relevant photosensitizer 3-(1′-hexyloxyethyl) pyropheophorbide-a (HPPH) is current in clinical trials for non-small cell bronchogenic carcinoma and early stage cancer of the larynx [50, 51] and was previously reported to have 100% tumor response in xenograft mice bladder cancer model at the dose of 0.5 mg/kg. In our study, we used 5 mg pyropheophorbide a /kg, which was chosen to match polymer concentration used to achieve the therapeutic DOX dose (2.5 mg/kg) in mice with our standard formulation (1 mg DOX/10 mg PNP or 2 mg pyropheophorbide a /ml).…”
Section: Discussionmentioning
confidence: 99%